In Autoimmune Diabetes Unique Autoreactive T Cells Recognize Insulin Peptides Generated in the Islets of Langerhans - Mohan, James F. (2010)
Besides the genetic framework, there are two critical requirements for the development of tissue-specific autoimmune diseases. First, autoreactive T cells need to escape thymic negative selection. Second, they need to find suitable conditions for autoantigen presentation and activation in the target tissue. We show here that these two conditions are fulfilled in diabetic NOD mice. A set of autoreactive CD4(+) T cells specific for an insulin peptide, with the noteworthy feature of not recognizing the insulin protein when processed by the antigen presenting cells (APC) escape thymic control, participate in diabetes and can cause disease. We also find that APCs situated in close contact with the beta cells in the islets of Langerhans bear vesicles with the antigenic insulin peptides and activate the peptide-specific T cells. These findings may be relevant for other cases of endocrine autoimmunity.